2015
DOI: 10.1097/md.0000000000000693
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Hypertension-Associated MicroRNAs in the Plasma of Patients With White Coat Hypertension

Abstract: White coat hypertension (WCH) is a high cardiovascular risk condition, and a fundamental understanding of the cause and pathophysiology of the disorder is still lacking. Recent studies demonstrated that microRNAs (miRNAs) are involved in hypertension; however, the roles of miRNAs in WCH are not known.The expressions of selected 10 miRNAs were investigated independently in plasma samples from 30 hypertension (HT) patients, 30 WCH patients, and 30 normotensive (NT) subjects.MiR-21, miR-122, miR-637, and let-7e e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 31 publications
(44 reference statements)
1
35
0
Order By: Relevance
“…It could act as a suppressor regulated on follicular thyroid carcinomas, ovarian cancer, and hepatocellular carcinoma, and it also participated in the differentiation of cells, such as human mesenchymal stem cells, migration and invasion of glioma cell, and human pancreatic ductal adenocarcinoma cells via suppressing Akt1 expression . At the same time, hsa‐miR‐637 can performed as a marker of follicular thyroid cancer, even hypertension . In the ATP6V0A1 polymorphism, the miR‐637 expression has been associated with EH development .…”
Section: Discussionmentioning
confidence: 99%
“…It could act as a suppressor regulated on follicular thyroid carcinomas, ovarian cancer, and hepatocellular carcinoma, and it also participated in the differentiation of cells, such as human mesenchymal stem cells, migration and invasion of glioma cell, and human pancreatic ductal adenocarcinoma cells via suppressing Akt1 expression . At the same time, hsa‐miR‐637 can performed as a marker of follicular thyroid cancer, even hypertension . In the ATP6V0A1 polymorphism, the miR‐637 expression has been associated with EH development .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study aiming to investigate the differential expression of hypertension‐associated miRs in the plasma of patients with white coat hypertension revealed that miR‐21, miR‐122, miR‐637, and let‐7e are up‐regulated in hypertensive subjects, whereas miR‐122 and miR‐637 are higher in white‐coat patients than in control subjects (Cengiz et al, ). BP values were negatively correlated with miR‐296‐5p.…”
Section: Hypertension and Mirsmentioning
confidence: 99%
“…Moreover, high titres of CMV have been found in hypertensive patients, leading to the speculative conjecture that CMV could contribute to hypertension by modulating miR pathways. A recent study aiming to investigate the differential expression of hypertension-associated miRs in the plasma of patients with white coat hypertension revealed that miR-21, miR-122, miR-637, and let-7e are up-regulated in hypertensive subjects, whereas miR-122 and miR-637 are higher in whitecoat patients than in control subjects (Cengiz et al, 2015). BP values were negatively correlated with miR-296-5p.…”
Section: Hypertension and Mirsmentioning
confidence: 99%
“…As a tumor suppressor microRNA, the plasma levels of let-7e are downregulated in malignant germ cell tumors, retinoblastoma, and esophageal adenocarcinoma (5)(6)(7). Let-7e is also associated with cardiovascular diseases; let-7e expression levels were significantly upregulated in patients with hypertension (8) and ischemic stroke during the acute stage (9), and downregulated in patients with ventricular septal defect (10). In addition, let-7e is associated with the number of metabolic syndrome Circulating microRNA let-7e is decreased in knee osteoarthritis, accompanied by elevated apoptosis and reduced autophagy traits (11), and the expression levels of let-7e are significantly increased in patients with Hashimoto's disease (12).…”
Section: Introductionmentioning
confidence: 99%